Casebook on general management in Asia Pacific (Basingstoke : Macmillan Business, 1999)
Western businesses in Asia Pacific. Asian businesses in Asia Pacific. Asian businesses in global competition.
Keywords: Business; Management; Enterprises; International business enterprises -- Management; Management -- Asia